Gender equality in New Zealand science: A 2011 snapshot - Bray, Belinda; Timewell, Emma (New Zealand Science Review, 2011)
​The Association for Women in the Sciences (AWIS) recently published a snapshot of Women in Science in New Zealand. This did not provide an in-depth analysis of trends, problems or achievements, but is intended to provide readers – whether involved in scientific research, man-agement, or policy – an overview of the current state-of-play. This article provides a summary of some of the findings.